Pengaruh Kesulitan Keuangan, Kondisi Industri Dan Pergantian Auditor Terhadap Kecurangan Laporan Keuangan - Fenny Marietza; Tommy (JRB-Jurnal Riset Bisnis, 2022)
This study aims to examine the effect financial distress, nature of industry and change in auditor on fraudulent financial reporting. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study is manufacturing companies that have reported the company's annual report. The analytical tool used in this study is SPSS version 25. The results showed that there was a negative influence between financial distress and fraudulent financial reporting and found no influence between nature of industry and change in auditor on fraudulent financial reporting. This research provides information about the worse the company’s financial condition can be the higher probability of the company committing fraudulent financial reporting. So that it becomes a consideration for companies in making policies to avoid the occurrence of fraudulent financial reporting. Keywords : Financial Distress, Nature of Industry, Change in Auditor, Fraudulent Financial Reporting